More Gas, Less Coal, and Less CO2? Unilateral CO2 Reduction Policy with More than One Carbon Energy Source - Julien Xavier Daubanes; Fanny Henriet; Katheline Schubert (Center for Economic Studies and ifo Institute (CESifo), 2017)
We examine an open economy's strategy to reduce its carbon emissions by replacing its consumption of coal—very carbon intensive—with gas—less so. Unlike the standard analysis of carbon leakage, unilateral carbon-reduction policies with more than one carbon energy source may turn counter-productive, ultimately increasing world emissions. Thus, we establish testable conditions as to whether a governmental emission-reduction commitment warrants the exploitation of gas, and whether such a strategy increases global emissions. We also characterize the extent to which this unilateral policy makes the rest of the world's emission commitments more difficult to meet. Finally, we apply our results to the case of the US.
Keywords: Q41; Q58; H73; F18; 330; unilateral climate policy; carbon emission reduction; shale gas; gas-coal substitution; coal exports; carbon leakage; US policy; counter-productive policy